El teatro argentino como registro de las nuevas migraciones - Perla Zayas de Lima (Les Cahiers ALHIM)
From de beginning of the Twentieth Century, Argentina has always shown a high level of intolerance and rejection towards immigration. This phenomenon is clearly represented in the theatre scene. Our analysis will focus on the way Argentines define themselves in opposition to these immigrants, the Europeans, their Latin American neighbours and later the Asian community.